Reconstruction of Global Moral Values Through Anthony Giddens' Structuration Theory in Responding to Ethical Diversity in the Modern Era - Miftakhur Rohman (Aqlania, 2025)
It is often said that "modern humans have lost moral values". It can be seen that the benchmark for whether a person can be said to be moral or not is from a pre-modern (traditional) point of view. This research tries to show that morals are part of the traditions and culture that are believed and agreed upon by humans in that group. However, it is permissible for other groups to have different moral agreements. This research is qualitative research whose aim is to reveal how moral principles are formed and whether they are dynamic or static considering the rapid development of the times. The results of this research found that morals are a product of tradition and culture which are dynamic, especially in the context of ethnic, religious and other diversity which should have values ​​that can unify diversity. Another important thing that was discovered was that in fact, in this diversity, all religions call for mutual respect and maintaining peace through good deeds while adhering to the values ​​of togetherness and harmony. In the end, these values ​​should always be instilled in every human being to behave and behave in society.